An Experimental Method to Determine the Impact Energy Absorption Capacity of Soils: Factors Affecting the Impact Energy Absorption of Sandy Soils - Selman Kahraman; İnan Keskin; Halil İbrahim Yumrutas; Ismail Esen (Buildings)
Energy absorption capacity (EAC) is a parameter that expresses how much energy materials can store or dissipate under an external load or impact. EAC plays a critical role in understanding soil deformations and dynamic stability under impact loads (e.g., falling masses, projectile penetration, blast impacts, or vehicle collisions). Impact loads are sudden and high-accelerated forces that cause soils to deform rapidly and absorb energy differently. Understanding the EAC of soils under impact loads is critical for various geotechnical applications, particularly understanding soil behavior under blast loads, which is critical for military and civil structures, and the reinforcement of soils and design of protective structures that will be subjected to similar sudden impacts. This study aims to develop a novel experimental method and apparatus to evaluate the EAC of sandy soils under controlled laboratory conditions. A custom-designed test device was used to measure impact forces exerted by a metal sphere dropped from a fixed height onto soil samples with varying grain sizes (coarse, medium, and fine) and relative densities (40%, 70%, and 90%) under different moisture conditions (dry, optimum, and wet). The results showed that fine-grained sands exhibited the highest EAC, with absorbed energy values reaching 23.15 J, while coarse-grained sands under dense and saturated conditions exhibited the lowest capacity (22.05 J). An increase in moisture content from dry water content to optimum water content resulted in a moderate increase in energy absorption followed by a slight decrease under saturated conditions. Similarly, higher relative density marginally reduced energy absorption, reflecting reduced soil deformation at higher densities. The study introduces a potentially standardizable testing procedure for assessing soil impact response, providing valuable insights for geotechnical engineering applications, including soil stabilization, pavement design, and impact-resistant infrastructure.